Pengaruh Tingkat Energi Micowave Sebagai Alat Desinfeksi Terhadap Kekuatan Kompresi Dental Stone - Amalia, Elsa, drg. Noor Hafida W, Sp.KG, drg. Ariyani Faizah, MDSc (2016)
Dental stone were used in dentistry for the preparation of die model for oral and maxillofacial structures and as important auxiliary materials for dental laboratory operations that are involved in the production of dental prostheses the stone has adequate compressive strength. Compressive strength that is important for hardness, facture and abrasion resistance. Die model can be sources of cross contamination that was caused by blood and saliva. Microwave is a toll that used as disinfection method. The purpose of this research was to know the influence of microwave energy level as disinfection method toward compressive strength dental stone. A cylindrical samples dental stone with dimensions 20 mm in diameter and 40 mm in height, were divided into 4 main groups. Group 1 without disinfection, group 2 disinfection with microwave 600 watt for 7 minutes, group 3 disinfection with microwave 800 watt for 7 minutes, group 4 disinfection with microwave 1000 watt for 7 minutes. The sample were tested compressive strength by using a UTM after 24 hours after mixing. The results mean of the highest compressive strength in the Group 2 compared to the other groups (17.59 MPa) and one way ANOVA analysis showed that there was no significant difference between them (P=0.097). Conclusion of this research was the energy level microwave has no effect against the compressive strength of dental stone, the most microwave energy level on the dental stone with right compressive strength is 600 watts.